Perencanaan Infrastruktur Riau: Mewujudkan Visi Riau 2020 - Ikhsan, Muhammad (JIP ( Jurnal Industri dan Perkotaan ), 2003)
Several backgrounds of infrastructure condition in Riau including geography, existing infrastructure and the people's condition will be presented in this paper.